(untitled) - Paretsky, Sara (New York, NY, 2018)
"Sara Paretsky follows her instant New York Times bestseller, Fallout - her most widely read novel in years - with an extraordinary adventure that pits her acclaimed detective, V.I. Warshawski, against some of today's most powerful figures"--
"Sara Paretsky follows her instant New York Times bestseller Fallout--her most widely read novel in years--with an extraordinary adventure that pits her acclaimed detective, V.I. Warshawski, against some of today's most powerful figures. Legendary sleuth V.I. Warshawski returns to the Windy City to save an old friend's nephew from a murder arrest. The case involves a stolen artifact that could implicate a shadowy network of international criminals. As V.I. investigates, the detective soon finds herself tangling with the Russian mob, ISIS backers, and a shady network of stock scams and stolen art that stretches from Chicago to the East Indies and the Middle East. In Shell Game, nothing and no one are what they seem, except for the detective herself, who loses sleep, money, and blood, but remains indomitable in her quest for justice"--
Booklist
BookPage
Library Journal
Publishers Weekly
Adult
Keywords: Fiction; Women detectives; Fiction; Criminal investigation; Fiction; Mystery; Illinois; Fiction; Women private investigators; Warshawski, V. I. (Fictitious character); Mystery fiction; Detective and mystery fiction; Mystery fiction; Detective and mystery stories